Perforated marine and freshwater snail shells as an indication of regional exchange systems during the Mesolithic in Croatia - Komšo, Darko; Miracle, Preston; Karavanić, Ivor; Vukosavljević, Nikola (2010)
Perforated shells figure prominently in discussions of exchange systems and body ornamentation during the Mesolithic in Europe. In this paper we discuss assemblages of perforated snail shells recovered from recent excavations of Mesolithic sites in Croatia. Numerous finds are found in several sites in Istria on the Adriatic coast and in cave Zala in Croatia's inland region of Lika. Perforated marine and freshwater snail shells from both regions suggest the existence of regional exchange systems during the Mesolithic between coastal and inland areas.
Projekt MZOS
ENG